HMBG1 as a Driver of Inflammatory and Immune Processes in the Pathogenesis of Ocular Diseases - Yi Liu; Guo-Bin Zhuang; Xue-Zhi Zhou (Journal of Ophthalmology)
High-mobility group box 1 (HMGB1) is a nuclear protein that can also act as an extracellular trigger of inflammation, proliferation, and migration in eye diseases. It induces signaling pathways by binding to the receptor for advanced glycation end products (RAGE) and Toll-like receptors (TLRs) 2, 4, and 9. This proinflammatory activity is considered to be important in the pathogenesis of a wide range of ocular diseases resulting from hemodynamic changes, presence of neovascular endothelial cells, secretion of intraocular immune factors or inflammation, and apoptosis of retinal cell layers. Further work is needed to elucidate in detail how HMGB1 contributes to ocular disease and how its damaging activity can be modulated. In this review, we summarize current knowledge on HMGB1 as a ligand that can evoke inflammation and immune responses in ocular diseases.